Pemberdayaan Produksi dan Pemasaran Kelompok Usaha Kuliner Dapoer Wanda di Bagirati, Cakranegara, Lombok - Irwan Syuhada; I Putu Dedy Arjita; I Putu Agus Santana (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This community service program was carried out to answer the production and marketing challenges faced by the Dapoer Wanda Culinary Business Group in Bagirati, Cakranegara, Lombok, a culinary MSME that focuses on boxed rice and betutu chicken products. The purpose of the activity is to increase production capacity, strengthen business management, and expand marketing reach through digitalization. The service method uses a participatory approach that involves socialization, training, application of appropriate technology, mentoring, and evaluation. The service team consisted of lecturers from Al Azhar Islamic University Mataram supported by students. The results of the activity showed an increase in partner understanding from 30% to 80%, an increase in production, and an average increase in sales by 25%. The uniqueness of this program lies in the integration of modern production technology with local content-based digital marketing strategies. The recommendations are directed at ongoing mentoring and strengthening multi-stakeholder collaboration to ensure the sustainability of service results